Adult acute rhinosinusitis guidelines worldwide: similarities and disparities. Issue 8 (2nd May 2018) - Gluck, Ofer; Marom, Tal; Shemesh, Shay; Tamir, Sharon Ovnat
Abstract : Background: Acute rhinosinusitis (ARS) is a common respiratory infection that poses a major public healthcare burden with respect to antibiotic consumption and related morbidity. Position statements and national ARS guidelines have been published worldwide, aiming to define diagnostic criteria and outline treatment options. Our objective was to analyze the similarities and disparities between such guidelines. Methods: We conducted an electronic database search for ARS guidelines using relevant keywords between January 1, 1989, through December 31, 2017. Overall, 25 guidelines from 39 countries were retrieved: 8 from 8 developed countries, and 17 from 31 developing countries. Representative guidelines from developing and developed countries from America, Europe, Africa, Asia, and Oceania were evaluated. We compared the bibliographic data, diagnostic criteria, and treatment recommendations of selected guidelines. Results: In most developed countries, otorhinolaryngological societies published ARS guidelines, whereas the Ministry of Health formulated the guidelines or adopted generic guidelines prepared by an international organization in developing countries. Many similarities in the diagnostic criteria were found, such as purulent nasal discharge and nasal obstruction sensation. In contrast, maxillary culture as a diagnostic tool was mentioned in developed countries, while it was generally ignored in developing countries. The watchful waiting (WW) policy and abstaining from immediate antibiotics was unanimously adopted in developed countries, which was only partly embraced in developing countries. The recommended universal first‐line antibiotic therapy is amoxicillin, with or without clavulanic acid, whereas options for second‐line and third‐line antibiotic therapies varied. Conclusion: ARS guidelines from different countries have many similarities. Specific recommendations are tailored to local epidemiology and healthcare accessibility.